Comparison of the effects of L-type calcium channel antagonist Amlodipine with L/N-type calcium channel antagonist Cilnidipine on blood pressure, heart rate, proteinuria and lipid profile in hypertensive patients (Bangladesh Journal of Medical Science, 2016)
Background: Cilnidipine is a novel and unique 1,4-dydropyridine derivative calcium antagonist that exerts potent inhibitory actions not only on L-type but also on N-type voltage dependent calcium channels. Blockade of the neural N-type calcium channel inhibits the secretion of norepinephrine from peripheral neural terminals and depresses sympathetic nervous system activity.Objective and methods: The purpose of this study was to assess the effect of Cilnidipine and Amlodipine on blood pressure (BP) levels. We did BP monitoring before and after once-daily use of Cilnidipine and Amlodipine in 100 hypertensive patients.Results: Both drugs significantly reduced systolic BP (SBP) and diastolic BP (DBP). However, the reductions in pulse rate (PR) were significantly greater in the Cilnidipine group than the Amlodipine group. N-type calcium channel blockade by Cilnidipine may not cause reflex tachycardia, and may be useful for hypertensive treatment.Conclusion: There was significant reduction in proteinuria with Clindipine as compared to Amlodipine. However, there were no significant change in total cholesterol level in diabetes and non-diabetics in both the group.Bangladesh Journal of Medical Science Vol.15(3) 2016 p.460-465